Cattle Breeding Waste Impact upon the Lake Sevan River Basin Systems Environmental State - Vardui G. Margaryan; Ovik Y. Sayadyan; Yekaterina V. Gaydukova; Nataliya L. Frolova; Levon V. Azizyan; Gorik D. Avetisyan (Водное хозяйство России: проблемы, технологии, управление)
The article is devoted to the environmental issues of Lake Sevan and the issues of the impact of animal waste on the environmental conditions of rivers in the drainage basin of Lake Sevan. The influence of biogenic elements, especially such as nitrogen and phosphorus, accelerates the processes of eutrophication of river sections that are under direct or indirect contact with fresh manure or incompletely processed animal waste. The situation is especially worse during the winter low-water runoff, when the livestock is mainly in barns and a concentrated large part of the manure, and its liquid mass is simply poured into the rivers. In winter, water discharges in the rivers of the Lake Sevan basin sharply decrease (comprising 5–24% of the average annual flow), which is because the rivers are mainly fed by groundwater.